Promoting reflective thinking through journal assignment in Edmodo - FX. Risang Baskara (Jurnal Linguistik Terapan, 2017)
This research was an investigation to explore the use of Edmodo as a reflective platform in the learning processes of English as a Foreign Language (EFL) students. The students made use of Edmodo as a platform to critically reflect on their learning processes. Thirty-five students in Information and Technology class in Sanata Dharma University in Yogyakarta participated in this research. One lecturer created an Edmodo account for use as a journal assignment so that the student could engage in and examine their own reflection process. The data collected were qualitative, consisting of students’ posting messages and comments on the Edmodo, surveys on the students’ reflective experiences using Edmodo as reflection tools, and group reflective dialogues recorded by lecturer in class meetings over the implementation of Edmodos during the course. The positive implications for the use of Edmodo as a medium to provide and promote critical reflection for EFL students were also investigated.